2020
DOI: 10.1049/iet-epa.2020.0318
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of an outer rotor permanent magnet synchronous generator with fractional winding for micro‐wind turbines

Abstract: Permanent magnet synchronous generators (PMSGs) have been widely used in micro‐wind turbines (MWTs) for direct‐drive applications. The generating maximum power from the PMSGs used in the MWTs is desired. However, cogging torque (CT) and design form of the PMSGs prevent this. Therefore, various methods are applied to reduce the CT of PMSGs in the literature. Some of them are inapplicable and some are the ones that cause power loss. In this study, to overcome the expressed causes, a new design, fabrication, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Through the power generation analysis, the output power has a positive correlation with the wave height, which becomes strong. The process is able to facilitate controlling the electricity FIGURE 16 The largest tidal power plant in the World [84] FIGURE 17 Schematic diagram of the wave power generation process [90] balance among the energy conversion storage. A comparative literature highlighting the contributions in existing relevant literature reviews compared to the proposed solar energy system.…”
Section: Tide and Wave Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Through the power generation analysis, the output power has a positive correlation with the wave height, which becomes strong. The process is able to facilitate controlling the electricity FIGURE 16 The largest tidal power plant in the World [84] FIGURE 17 Schematic diagram of the wave power generation process [90] balance among the energy conversion storage. A comparative literature highlighting the contributions in existing relevant literature reviews compared to the proposed solar energy system.…”
Section: Tide and Wave Energymentioning
confidence: 99%
“…This review provides literature documentation regarding environmental challenges concerning sustainable and renewable energy resources. In the author's earlier reports [17][18][19][20][21][22], it was suitable for sustainable development. Bi 2 Te 3 -and Bi 2 Te 3based nanostructure materials for review and experimental studies on growth, characterization, and performance evaluation were found to be more suitable for device manufacturing than thin films for long-term utilization in other studies [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%